Social and asocial dimension of journalism in modern mass communication. For the 100th anniversary of Juozas Prunskis - fakultetas, Komunikacijos (Žurnalistikos tyrimai, 2007)
Vilnius University, Small Hall, 2007 12 07. [A. Vaišnys announced the concept of a new Vilnius University journal dedicated to media research]. On December 7, 2007, Vilnius University hosted the conference “The Social and Antisocial Dimensions of Journalism in Modern Mass Communication” to mark the centenary of diaspora journalist Juozas Prunskis. The event explored journalism’s societal roles and ethical boundaries, highlighting the contrast between socially responsible journalism and manipulative, antisocial media practices. Participants discussed the ethical foundations and civic mission of journalism in contemporary communication. During the event, Prof. Dr. Andrius Vaišnys introduced the concept for a new Vilnius University academic journal dedicated to media research—an important initiative to strengthen journalism studies in Lithuania.